2013
DOI: 10.1016/j.psyneuen.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term programming of enhanced aggression by peripuberty stress in female rats

Abstract: Summary Human literature has linked adverse early life experiences with an increased risk to develop violent behaviors in both boys and girls. We have previously shown that male rats submitted to stress during the peripuberty period display as adults abnormal aggressive behavior against both male intruders and female partners. In the present study, we examined whether the same stress protocol would affect the development of aggressive behaviors in female rats. We evaluated the behavior of these peripuberty str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 57 publications
7
32
0
Order By: Relevance
“…Pregnant adverse stimulus including physico-chemical and biological factors during fetal development may induce long-term structural and functional effects and yield programming/imprinting effects to cause diseases (Kaplan et al, 2011;Ruchat et al, 2013;Cordero et al, 2013;Vickers, 2014;Kilcoyne et al, 2014;Krow-Lucal et al, 2014). The present study revealed that prenatal exposure to SEB significantly increases the CD4:CD8 T-cell ratio through the decrease of CD8 T cells and the increase of CD4 T cells in the peripheral blood of both neonatal and adult offspring rats.…”
Section: T Zhang and Othersmentioning
confidence: 47%
“…Pregnant adverse stimulus including physico-chemical and biological factors during fetal development may induce long-term structural and functional effects and yield programming/imprinting effects to cause diseases (Kaplan et al, 2011;Ruchat et al, 2013;Cordero et al, 2013;Vickers, 2014;Kilcoyne et al, 2014;Krow-Lucal et al, 2014). The present study revealed that prenatal exposure to SEB significantly increases the CD4:CD8 T-cell ratio through the decrease of CD8 T cells and the increase of CD4 T cells in the peripheral blood of both neonatal and adult offspring rats.…”
Section: T Zhang and Othersmentioning
confidence: 47%
“…Adverse experiences in early life such as neonatal maternal separation cause long-lasting behavioral and psychological effects, and the effects of neonatal experience can remain detectable in the aged (Akers et al., 2008, Arborelius and Eklund, 2007). Neonatal and pubertal stress experiences have no small effect on the development and maturation of the HPA axis, and cause organizational effects resulting in changes in emotional function and the stress response (Cordero et al., 2013, Romeo, 2010, Romeo, 2003). Our findings showed the long-term influence of stress experience in young adulthood on stress responses in old age.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we did not explicitly include a cohort exposed to stress during the intermediate period comprising P34 and P36, which corresponds to the onset of puberty in female rats. However, as female rats exposed to the Full Peripubertal Stress also develop increased aggression, 59 it will be important in future studies to investigate potential sex differences linked to the timing and chronicity of stress exposure during the developmental periods under study.…”
Section: Discussionmentioning
confidence: 99%